Diseño del sistema estructural de una radiobase digital adaptable a tres tipos de tarjetas electrónicas de iDEN - Barrientos-Carvajal, Melissa (Instituto Tecnológico de Costa Rica, 2018)
The radiocomunication company Multicom, has an unused stock of three different models of electronic motherboards, consisting of 100 units per each model for a total of 300 motherboards. These cards belong to potable radios whose body and other components are not in proper operation and it is not possible to obtain spare parts for their repair. The company has to revalue the cards in the form of a communication radio base. This project proposes a new model of a estructural system or case for a radio base, to which each one of the three different models of electronic cards can be adapted. The design includes aspects of usability, ergonomics, disposition of internal elements, consideration of materials and components, manufacturing methods, among other important aspects, in order to satisfy the needs of different users, adapt the product to different contexts of use, and comply with the requests from the company.
Proyecto de Graduación (Bachillerato en Ingeniería en Diseño Industrial) Instituto Tecnológico de Costa Rica, Escuela de Diseño Industrial, 2018
Keywords: Radio base; Tarjeta madre; Carcasa; Radio; Tarjetas; Estructura; Research Subject Categories::TECHNOLOGY::Information technology::Computer science::Computer science